The Impact During of Pandemic COVID-19 on Property Sector Case Study: DKI Jakarta Province - Arkandana, M. Tharif; Mariel, Wahyu Calvin Frans; Pramana, Setia (Jurnal Ikatan Sarjana Ekonomi Indonesia, 2022)
Since the COVID-19 pandemic in Indonesia, economic conditions have declined, especially in the property sector but if we look at the distribution value of the real estate sector in 2020 during the pandemic, its contribution has increased to 6.31% after falling by 5.94% in 2019. Another impact is that the Property Price Index growth value decreases over the years, but in a big city like DKI Jakarta, it does not affect the pandemic condition. Big Data has the potential to produce useful and useful statistics and assist in the collection of Official Statistics data. This study aims to see the condition of the number of advertisings on the property side and the selling price of houses and apartments that can be impacted by the pandemic COVID-19. Based on data from one property site in Indonesia, the condition of ad serving during the pandemic is very influential, with the highest serving during the Micro Indonesia large-scale social restrictions (PSBB).